Transformasi Digital dalam Studi Tafsir: Potensi, Distorsi, dan Tanggung Jawab Akademik - Muhammad Rafsanjani; Muhammad Arwani Rofi’i; Ulfatul Halimah (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2026)
The emergence of digital technology has fundamentally revolutionized how Muslims access, study, and disseminate the Qur'anic exegesis (tafsir). The digitization of interpretations poses three risks: loss of text authenticity, decreased validity of interpretations due to truncated context, and weakened scientific authority as interpretations are determined more by algorithms than by the competence of scholars. This article critically examines the dynamics of this digital transformation, highlighting the serious risk of semantic distortion that arises from truncated texts, decontextualized summaries, or inconsistencies with the original intent of the mufassir. Utilizing a qualitative study of popular Indonesian digital platforms, the research reveals that although accessibility has increased, certain digital content fails to fully adhere to authoritative texts and often neglects established methodological principles of interpretation. These findings emphasize the necessity of academic responsibility in harmonizing technological advancement with scholarly integrity, concluding that the digital transformation in tafsir studies can only yield positive contributions if strictly managed through rigorous academic control and ethical scholarship, necessitating wider digital tafsir literacy among users.